Incorporating muslim migrants in western nation states: a comparison of the United Kingdom, France, and Germany - Koenig, Matthias (After integration, 2015)
Only recently has the religious dimension of international migration and integration moved up on the agenda of academic research and public policy. For a long time, and by following mainstream theories of secularization, both researchers and policy-makers tended to assume that traditional and religious attitudes of immigrants would successively dissolve in the process of acculturation and assimilation to industrial societies. Similar assumptions were shared by theorists of multiculturalism who stressed that migration processes were accompanied by new claims for recognition of particularistic cultural or ethnic identities, but ignored the specifically religious dimensions of such identities.